What regulatory policies work for emerging markets? - Luo Ping (Asian Development Bank Institute (ADBI), 2011)
This paper discusses the banking regulatory and supervisory practices in People's Republic of China (PRC) with reference to the international standard for banking supervision, namely, the Basel Core Principles for Effective Banking Supervision (BCPs). While the PRC has incorporated many sound practices advocated by the BCPs, there are quite a few areas where significant differences can be observed with respect to qualification review of senior management, broader regulation at the product level, prescriptive rules, and guidance for risk management. Broadly speaking, the PRC adopts a rules-based approach to regulation; in many cases, regulations are prescriptive or even intrusive. In building a robust supervisory system, the PRC finds specific guidance more helpful than sole reliance on principles-based approaches. The paper argues that general principles and a principle-based approach to regulation do not seem to work well for emerging markets. Indeed, the current financial crisis has revealed some shortcomings in the existing international standards on banking supervision. Perhaps this standard can be improved by greater specificity and by incorporating more aspects of the experiences in emerging markets.
Keywords: G20; G28; 330; Bankenpolitik; Bankenaufsicht; China; Vergleich; Basel II